Dietary Patterns Impact Temporal Dynamics of Fecal Microbiota Composition in Children With Autism Spectrum Disorder - Berding, Kirsten; Donovan, Sharon M. (Frontiers in Nutrition, 2020)
Environmental factors such as diet are known influencers on gastrointestinal (GI) microbiota variability and some diseases are associated with microbial stability. Whether microbial variability is related to symptoms of Autism Spectrum Disorder (ASD) and how diet impacts microbial stability in ASD is unknown. Herein, temporal variability in stool microbiota in relation to dietary habits in 2–7 years-old children with ASD (ASD, n = 26) and unaffected controls (CONT, n = 32) was investigated. Fecal samples were collected at baseline, 6-weeks and 6-months. Bacterial composition was assessed using 16S rRNA sequencing. Short fatty acid (SCFA) concentrations were analyzed by gas chromatography. Nutrient intake was assessed using a 3-day food diary and dietary patterns (DP) were empirically derived from a food frequency questionnaire. Social deficit scores (SOCDEF) were assessed using the Pervasive Developmental Disorder Behavior Inventory-Screening Version (PDDBI-SV). GI symptoms were assessed using the GI severity index. Overall, temporal variability in microbial structure, and membership did not differ between the groups. In children with ASD, abundances of Clostridiaceae, Streptophyta, and Clostridiaceae Clostridium, varied significantly, and concentrations of all SCFAs decreased over time. Variability in community membership was negatively correlated with median SOCDEF scores. Additionally, Clostridiales, Lactococcus, Turicibacter, Dorea, and Phascolarctobacterium were components of a more stable microbiota community in children with ASD. DP1, characterized by vegetables, starchy vegetables, legumes, nuts and seeds, fruit, grains, juice and dairy, was associated with changes in species diversity, abundance of Erysipelotricaceae, Clostridiaceae Clostridium, and Oscillospira and concentrations of propionate, butyrate, isobutyrate and isovalerate in children with ASD. DP2 characterized by fried, protein and starchy foods, “Kid's meals,” condiments, and snacks was associated with variations in microbiota structure, abundance of Clostridiaceae Clostridium, and Oscillospira and changes in all SCFA concentrations. However, no association between microbial stability and SOCDEF or GI severity scores were observed. In conclusion, microbiota composition varies over time in children with ASD, might be related to social deficit scores and can be impacted by diet. Future studies investigating the physiological effect of the changes in specific microbial taxa and metabolites are needed to delineate the impact on ASD symptomology.